Sistem penanggalan Hijriah Mohammad Shawkat Odeh - Muh. Nashirudin (State Institute of Islamic Studies (IAIN) Salatiga, 2011)
This paper discusses the Hejric calendar system by Mohammad Shawkat Odeh, one of Muslim astrono-mers from the Islamic world who offers new criterion for lunar crescent’s visibility and the Hejriccalendar system. This article describes and analyzes some concepts proposed by Odeh concerning hisab(calculation) and rukyah (moon-sighting) such as criteria for the crescent visibility. The criteria offered byOdeh is the result of a long-time research (from 1859 – 2005 and totalled 737 observations). TheUniversal Hejric Calendar proposed by Odeh divides the world into two zones: the westerns zonecovers American continent and the eastern zone covers Asian, African, Australian, and European conti-nents. Although there are some problems caused by the division of zones, the idea that most ofMuslim countries includes in the same zone is expected to reduce the problem of dissimilarity indetermining the new moon. Consequently, the unification of the first date of the month and also theIslamic calendar is possible.